2009
DOI: 10.1158/0008-5472.can-08-3037
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of γδ T Cells Reactive against Cytomegalovirus-Infected Cells in a Mouse Xenograft Tumor Model

Abstract: Abstract;D T cells recognize stress-induced autoantigens and contribute to immunity against infections and cancer. Our previous study revealed that VD2-negative ( neg ) ;D T lymphocytes isolated from transplant recipients infected by cytomegalovirus (CMV) killed both CMV-infected cells and HT29 colon cancer cells in vitro. To investigate the antitumor effects of VD2 neg clones in vivo, we generated hypodermal HT29 tumors in immunodeficient mice. Concomitant injections of VD2 neg clones, in contrast to VD2 + ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…25 Moreover, we recently reported on the ability of human CMV-specific V␦2 neg ␥␦ T cells to inhibit tumor cell development in vivo in a model of human tumor xenograft in immunodeficient mice. 26 Taken together, our previous findings have suggested that the ␥␦ T cells that were amplified during CMV infection may also be involved in tumor surveillance. In this report, we have examined the relationship between CMV-induced ␥␦ T cells and in vivo cancer occurrence in KTRs.…”
mentioning
confidence: 56%
“…25 Moreover, we recently reported on the ability of human CMV-specific V␦2 neg ␥␦ T cells to inhibit tumor cell development in vivo in a model of human tumor xenograft in immunodeficient mice. 26 Taken together, our previous findings have suggested that the ␥␦ T cells that were amplified during CMV infection may also be involved in tumor surveillance. In this report, we have examined the relationship between CMV-induced ␥␦ T cells and in vivo cancer occurrence in KTRs.…”
mentioning
confidence: 56%
“…In this context, the recent demonstration in a murine xenograft model that gd T cells, reactive against cytomegalovirus infected cells, exhibit anti-tumour activity is of interest. 22 The major cause of treatment failure in patients allografted for refractory AML is disease relapse. In this study, pre-transplant tumour burden is identified as an important determinant of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…17 Orthotopic xenografts of the HT29 colon cancer cells in mice infused with human TCRVd2 2 cd T lymphocytes also carried cd TILs that impaired tumor development. 18 In prostate and breast tumors, however, Vd1 1 cd TILs are rather immunosuppressive for dendritic cells and T cells 19 and favor the growth of the tumor through IL-10 release. 20 The second hallmark of T lymphocytes expected to attack tumors is their histocompatibility leukocyte antigen-unrestricted cytotoxic capacity for cancer cells, as well as their ability to secrete adequate cytokines.…”
Section: Rationale For Harnessing CD Cells In Cancer Immunotherapymentioning
confidence: 99%